2010
DOI: 10.1186/1471-2458-10-100
|View full text |Cite
|
Sign up to set email alerts
|

The French Observational Cohort of Usual Smokers (FOCUS) cohort: French smokers perceptions and attitudes towards smoking cessation

Abstract: BackgroundDespite increasing governmental anti-smoking measures, smoking prevalence remains at a high level in France.MethodsThe objectives of this panel study were (1) to estimate smoking prevalence in France, (2) to identify smokers' profiles according to their perceptions, attitudes and behaviour in relation to smoking cessation, (3) to determine predictive factors of quit attempts, and (4) to assess tobacco-related behaviours and their evolutions according to the changes in the smokers' environments. A rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
3
16
2
13
Order By: Relevance
“…A study in France found 'health' as a reason to quit on rank four with 24% [15] , and a recent Chinese study found the same reason to be on rank one with 55% [16] ; however, the authors affirm that considerably fewer Chinese smokers are willing to quit in international comparisons [17] . This high concern for health in the present study could be due to the setting of the treatment unit in a health centre and affiliated with a general practitioner's practice.…”
Section: Discussionmentioning
confidence: 82%
“…A study in France found 'health' as a reason to quit on rank four with 24% [15] , and a recent Chinese study found the same reason to be on rank one with 55% [16] ; however, the authors affirm that considerably fewer Chinese smokers are willing to quit in international comparisons [17] . This high concern for health in the present study could be due to the setting of the treatment unit in a health centre and affiliated with a general practitioner's practice.…”
Section: Discussionmentioning
confidence: 82%
“…In a review of the published literature before 2003, McCaul et al found that most smokers who have quit or who are thinking about doing so are mostly concerned about health problems (McCaul et al, 2006). Many studies confirm the fact that health concerns constitute a major motive, for adult smokers and even adolescents, to quit smoking beside other motives such as cost, esthetic, and athletic performance (Aubin et al, 2010;Aung, Hickman, & Moolchan, 2006;Sieminska et al, 2008;Yang, Fisher, Li, & Danaher, 2006;Youssef, Abou-Khatwa, & Fouad, 2003). Studies evaluating the motivation of smokers to quit smoking during or after being present in a hospital setting because of any health problem are numerous.…”
Section: Introductionmentioning
confidence: 93%
“…Craving has been suggested to be among the most important acute factors contributing to unsuccessful quitting or smoking relapse (Tiffany et al, 2009;Aubin et al, 2010;Killen et al, 2006;Killen and Fortmann, 1997;Piasecki, 2006), but it remains understudied. For example, no clear data on heritability of tobacco craving are available.…”
Section: Introductionmentioning
confidence: 99%